Human Capital Transformation in Equalizing Workloads and Increasing Employee Discipline: Study of the Regional Financial and Asset Agency of Takalar Regency - Nur Faidah; Miftahul Jannah Ilyas; Faizal; Muchriady Muchran (Masterpiece, 2026)
This study aims to analyze the role of Human Capital Transformation (HCT) as a strategic intervention to address workload disparities and improve employee discipline at the Regional Financial and Asset Management Agency (BKAD) of Takalar Regency. The main issues identified include unequal workload distribution—resulting in simultaneous conditions of overload and underload—as well as suboptimal employee discipline, particularly in terms of compliance with working hours and punctuality. This research employs a descriptive qualitative approach, with data collected through in-depth interviews with leaders and staff, observations, and document analysis, including policies on Workload Analysis (ABK) and the Performance Allowance (TPP) system. The findings indicate that the Human Capital Transformation implemented by BKAD is realized through two key mechanisms. First, the integration of ABK into the e-performance system and TPP, which significantly minimizes workload disparities by ensuring measurable and equitable task distribution. Second, the consistent enforcement of discipline based on digital data (electronic attendance), supported by the transparent application of sanctions and rewards in accordance with Government Regulation No. 94 of 2021. This transformation has proven to be a catalyst in creating a productive, performance-based, and integrity-driven work environment. The study concludes that Human Capital Transformation is a fundamental prerequisite for public sector organizations to achieve accountability and efficiency.